Pembaharuan Hukum Perdata di Indonesia - Aprita, Serlika (UIN Jakarta, 2021)
The politics of codification in the renewal of national civil law must also pay attention to the existence of the legal rules contained in Islamic law and customary law as sources that can be used as material in the renewal of national civil law. There are two important issues in the agenda of revising the national civil procedural law, that is; regarding aspects of evidence that must adapt to technological advances and various models of civil transactions, regarding the execution of court decisions which so far have failed to be executed in the absence of the involvement of law enforcement. For things that are not possible to be uniformed, they are left as they are now while still treating their respective customary and religious laws in accordance with what has been done with Law no. 1 of 1974 concerning marriage.